Post-Last Glacial Maximum settlement of the West Angelas region in the inland Hamersley Plateau, Western Australia. Issue 3 (2nd September 2017) - Slack, Michael; Connell, Kate; Davis, Annabelle; Gliganic, Luke Andrew; Law, W. Boone; Meyer, Michael
Abstract: An excavation and survey program at West Angelas, in the Pilbara region of Western Australia, shows that the poorly watered interior area of the Hamersley Plateau was first occupied soon after the conclusion of the Last Glacial Maximum, and that significant use of this area probably only occurred during the mid to late Holocene. Although current archaeological research shows that Aboriginal groups have occupied areas of the Hamersley Plateau for more than 40, 000 years, the permanent and prolonged use of the more marginal or ecologically suboptimal foraging environments of the interior plateau is a comparatively recent development in the region's long archaeological record.